Urgensi dan Fungsi Hadis dalam Pendidikan Islam - Mustofa, Ahmad Ali; Sayidah, Aminatus (TSAQOFAH, 2025)
Hadith is one of the sources of Islamic law that plays an important role in explaining and complementing the Qur'an. This article aims to examine the urgency and function of hadith in Islamic education, especially in explaining values that are not explicitly found in the Qur'an, and how hadith can be used as a basis for educational methodology. This study uses a literature approach by exploring various primary and secondary sources that discuss the function of hadith in education. The results of the study show that the hadith functions as explanatory, complementary, reinforcing, and limiting verses of the Qur'an, thus becoming an important foundation in building a holistic Islamic education system. In addition, the function of the hadith which includes explaining the law, strengthening moral values, and establishing a compassion-based learning methodology makes it relevant in the modern education system. The practical implication of this study is the importance of an in-depth understanding of hadith in designing an Islamic education curriculum that is oriented towards character building and spirituality.